1993
DOI: 10.1287/mnsc.39.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Timid Choices and Bold Forecasts: A Cognitive Perspective on Risk Taking

Abstract: Decision makers have a strong tendency to consider problems as unique. They isolate the current choice from future opportunities and neglect the statistics of the past in evaluating current plans. Overly cautious attitudes to risk result from a failure to appreciate the effects of statistical aggregation in mitigating relative risk. Overly optimistic forecasts result from the adoption of an inside view of the problem, which anchors predictions on plans and scenarios. The conflicting biases are documented in ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
440
2
9

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,696 publications
(457 citation statements)
references
References 43 publications
6
440
2
9
Order By: Relevance
“…For example, it has been suggested that the planning fallacy (viz, the tendency to underestimate task completion times) results from individuals' reliance on oversimplified representations of future tasks (Buehler et al, 1994;Kahneman & Lovallo, 1991;Kahneman & Tversky, 1979). A visit of the in-laws is not part of the scenario of writing a paper, and therefore would not be taken into account in estimating the paper's completion time, even if known in advance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been suggested that the planning fallacy (viz, the tendency to underestimate task completion times) results from individuals' reliance on oversimplified representations of future tasks (Buehler et al, 1994;Kahneman & Lovallo, 1991;Kahneman & Tversky, 1979). A visit of the in-laws is not part of the scenario of writing a paper, and therefore would not be taken into account in estimating the paper's completion time, even if known in advance.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large amount of research on how individuals predict the future and the factors that influence those predictions (see, e.g., Griffin, Dunning, & Ross, 1990;Kahneman & Lovallo, 1991;Sherman, 1980;Wilson, Wheatley, Meyers, Gilbert, & Axsom, 2000). However, this research has typically compared predictions with actual outcomes.…”
mentioning
confidence: 99%
“…Now consider what may happen as task or environmental complexity is increased. Research suggests that this discrete focus, induced via situational framing, may actually reduce the leaders' capacity to work with multiple causes and, in turn, hamper performance (Bercovitz, de Figuieredo, & Teece, 1997;Dosi, & Lovallo, 1997;Kahneman & Lovallo, 1993). Thus, it seems reasonable to believe that performance may vary by situational framing and complexity, leading to the third study hypothesis.…”
Section: Complexity and Leadershipmentioning
confidence: 98%
“…These could potentially include any psychological: overconfidence [49], optimism [50], hubris [28], narcissism [51], herd behavior [52], and culture heritage [53]. The literature on psychological characteristics and corporate risk-taking are shown in Table III. Behavioral decision theory suggests that hubris or overconfidence, as one type of cognitive bias, encourages decision makers to overestimate their own problem-solving capabilities [54], underestimate the resource requirements of risky initiatives [55], and underestimate the uncertainties facing their firms [56]. More importantly, people's psychological bias may generate the mode of thinking, the outlook on world, life and values which further influence one's decision-making and other behaviors.…”
Section: Psychological Bias and Risk-takingmentioning
confidence: 99%